How do fathers’ educational level contribute to children’s school problems? Overparenting and children’s gender and surgency in a moderated mediation model - Ruiz-Ortiz, Rosa María; Carreras, Rosario; del Puerto-Golzarri, Nora; Muñoz, José Manuel (Frontiers in Psychology, 2024)
This study aims to investigate (a) the mediating role of overparenting between father's educational level and children's school problems, and (b) the joint moderating role of children's gender and surgency in the indirect relationship between father's educational level and school problems. Participants were 203 schoolchildren, 96 boys (47.3%) and 107 girls (52.7%), aged 7-8 years (M = 92.42 months, SD = 3.52). Fathers reported their educational level, age and employment status and their children's gender and number of siblings, as well as their overparenting behaviors by Anticipatory Problem Solving (APS) scale. Teachers informed children's school problems by the Behaviour Assessment System for Children (BASC T-2). Parents together informed their children's surgency levels by a subscale of Children's Behaviour Questionnaire (CBQ). Results showed that, in girls, the father's educational level was negatively related to the child's school problems via overparenting behaviors, controlling the number of siblings and father's age and employment status. However, among boys, fathers' overparenting protect their shy sons from the risk of a low educational level for school problems. These findings highlight the relevance of considering the gender and surgency to a better understanding of the effects of contextual factors on children's outcomes. 1 Eliminado: Parents can play a crucial role in their children's school 79 readiness, contributing to their cognitive stimulation and motivation 80 for learning (Bandura, 1993). Indeed, 81 Eliminado: s 82 Eliminado: although several factors (e.g., income level, residential 83 status…) may be indirectly associated with children's adaptation to 84 academic activities (Varghese & Wachen, 2016), 85 Eliminado: ). For example, children whose fathers spend more time 86 and responsively interact with them have a better cognitive, language